A Retrospective Analysis of Nonocclusive Mesenteric Ischemia in Medical and Surgical ICU Patients: Clinical Data on Demography, Clinical Signs, and Survival. (November 2020) - Stahl, Klaus; Busch, Markus; Maschke, Sabine K.; Schneider, Andrea; Manns, Michael P.; Fuge, Jan; Wiesner, Olaf; Meyer, Bernhard C.; Hoeper, Marius M.; Hinrichs, Jan B.; David, Sascha
Background: To analyze demography, clinical signs, and survival of intensive care patients diagnosed with nonocclusive mesenteric ischemia (NOMI) and to evaluate the effect of a local intra-arterial prostaglandin therapy. Methods: Retrospective observational study screening 455 intensive care patients with acute arterial mesenteric perfusion disorder in a tertiary care hospital within the past 8 years. Lastly, 32 patients with NOMI were enrolled, of which 11 received local intra-arterial prostaglandin therapy. The diagnosis of NOMI was based on the clinical presentation and established biphasic computed tomography criteria. Clinical and biochemical data were obtained 24 hours before, at the time, and 24 hours after diagnosis. Results: Patients were 60.5 (49.3-73) years old and had multiple comorbidities. Most of them were diagnosed with septic shock requiring high doses of norepinephrine (NE: 0.382 [0.249-0.627] μg/kg/min). The Sequential Organ Failure Assessment (SOFA) score was 18 (16-20). A decrease in oxygenation (Pao 2 /Fio 2 ), pH, and bicarbonate and an increase in international normalized ratio, lactate, bilirubin, leucocyte count, and NE dose were early indicators of NOMI. Median SOFA score significantly increased in the last 24 hours before diagnosis of NOMI (16 vs 18, P < .0001). Overall, 28-day mortality was 75% (81% nonintervention vs 64% intervention cohort; P = .579). Median SOFA scores 24 hours after intervention increased by +5% in the nonintervention group and decreased by 5.5% in the intervention group ( P = .0059). Conclusions: Our data suggest that NOMI is a detrimental disease associated with progressive organ failure and a high mortality. Local intra-arterial prostaglandin application might hold promise as a rescue treatment strategy. These data encourage future randomized controlled trials are desirable.